International strategic alliance and organisational learning : factors for promoting learning : a Malaysian case - Mansor, Zuraina (2010)
Intense competition and the augmentation of business opportunities are amongst two major factors for the globalization of worldwide markets and economies. These trends are currently exploiting the industries manufacturing and non-manufacturing, calls them to take advantage of globalization process and to adopt a more sophisticated approach to strategic marketing and planning including performing collaboration. Companies have to constantly increase their knowledge base if they are to remain competitive. One way of increasing knowledge is by forming alliances. The purpose of this study is to identify the factors that promote learning through the formation of strategic alliances between a Malaysian manufacturing organisation with a UK partner and have included learning into their alliance objectives. It is a qualitative and in-depth studies of the company where the data collection process involved one time forum with personnel who were directly involved under the project, interviews with selected respondents, questionnaires, plant observation as well as secondary resources such as company reports and brochures.